Keragaman Plankton dan Kualitas Perairan di Hutan Mangrove - N. M. Heriyanto (Buletin Plasma Nutfah, 2012)
Plankton Diversity and Water Quality in Mangrove Forest. N.M. Heriyanto. Study the diversity of plankton and water quality in mangrove forests Blanakan was done in Subang, West Java and Cilacap, Central Java, in September 2010. Study used purposive random sampling method and the data were analyzed in the laboratory. The results showed five that different types of phytoplankton were found and a type of zooplankton that were Fragillaria sp., Navicula sp., Nitzschia sp., Surirella sp., Tabellaria sp., and one type of zooplankton Nauplius sp. Abundance of species (Di) Nitzschia sp. were found most dominant in the amount of 33.33% at the location of Cilacap and 25% in Blanakan, abundance of Fragillaria sp. 31.25% was in Blanakan and 11.11% in Cilacap. Plankton species diversity (H’) was generally low, the index of similarity (E) in the waters of relatively the same in both places. Mangrove forest at study site was dominated by Avicenia marina L. (Blanakan) and Rhizophora mucronata Blume (Cilacap). Heavy metal content of Hg in Cilacap was 7 times greater than Blanakan waters, the concentration of Zn in the same place two times larger, and cyanide (Cn) 4 times larger. Cilacap detergent in the water waw 12 times greater than these Blanakan waters. Water quality in industrial areas are generally worse than those in mangrove degraded areas. AbstrakPenelitian keragaman plankton dan kualitas perairan di hutan mangrove dilakukan di Blanakan Subang, Jawa Barat dan Cilacap, Jawa Tengah, pada September 2010. Penelitian menggunakan metode purposif random sampling dan data yang diperoleh dianalisis di laboratorium. Pada penelitian ditemukan lima jenis fitoplankton (Fragillaria sp., Navicula sp., Nitzschia sp., Surirella sp., Tabellaria sp.) dan satu jenis zooplankton (Nauplius sp). Kelimpahan jenis (Di) Nitzschia sp. paling dominan, yaitu 33% di Cilacap dan 25% di Blanakan, kelimpahan Fragillaria sp. 31% di Blanakan dan 11% di Cilacap. Keragaman jenis plankton (H’) umumnya rendah, indeks kesamaan (E) di perairan di kedua tempat relatif sama. Hutan mangrove di lokasi penelitian didominasi oleh jenis Avicenia marina L. (Blanakan) dan Rhizophora mucronata Blume (Cilacap). Kandungan logam berat Hg di Cilacap tujuh kali lebih besar dari perairan Blanakan. Konsentrasi Zn di tempat yang sama dua kali lebih besar, dan sianida (Cn) empat kali lebih besar. Deterjen di perairan Cilacap lebih besar 12 kali dibandingkan dengan perairan Blanakan. Kualitas perairan di kawasan industri umumnya lebih buruk dibandingkan dengan kawasan bermangrove terdegradasi.